γ-aminobutyric acid Rich Foods : methods for production and the effects of intake - Sjöblom, Agnes (SLU/Department of Molecular Sciences, 2021)
The current widespread interest in healthy lifestyle creates a demand for functional foods. New nutritious food products and supplements are launched on the market and products enriched with γ-aminobutyric acid (GABA) constitutes some of them. γ-aminobutyric acid is a widely present amino acid in plants, animals, fungi and microorganisms. It works as an inhibitory neurotransmitter in the central nervous system and is known for its calming effect. Multiple studies have shown a biologic response in humans after GABA administration including relaxation, inhibition of neuronal damage, prevention of neurological disorder, enhancement of sleep time, anti-hypertensive effect, antioxidant property and more. A development is seen regarding health promoting GABA enriched food products including tea, cheese and sourdough bread. The GABA production is often made using microorganisms, especially fermenting lactic acid bacteria in biosynthetic methods. Useful bacteria strains in fermented foods, such as kimchi and soy sauce, are found by companies as well as in scientific research with a goal to develop new healthy food products. The mechanism for oral GABA to affect human behaviour is not fully established. The ability of the GABA molecule to pass the blood brain barrier is disputed but other metabolic pathways are possible including the gut-brain-axis. In this literature study, several methods for GABA production and enrichment will be presented as well as the biochemical effects of intake of these products on the human body.